THE LEGEND OF THE TOMB OF THE CURSED DAUGHTER: WHERE DID IT ALL COME FROM? - Korchagin, P.A. (Perm Federal Research Centre Journal, 2016)
Since the late nineteenth century the urban legend about the cursed daughter has been known in Perm and associated with a cast-iron gravestone of a peculiar form situated on the Old Yegoshikha Cemetery. The gravestone has been repeatedly described in the works of A.P. Gaidar, M.A. Osorgin, A.D. Krasheninnikov and numerous newspaper articles. There is "Adam’s head" depicted on Taisia Deville’s (1800-1807) gravestone inscribed in a peculiar kind of frame - a snake biting its own tail. Perhaps the wrong interpretation of the symbols of eternity and salvation as symbols of sin, death and danger led to the emergence of stories about the Perm district police officer who cursed his daughter and the fruit of her unrequited love. The father of little Taisia, Alexander Ivanovich Deville, was in fact an educated Perm official at the turn of XVIII-XIX centuries, and her grandfather Jean-Louis de Velly, a famous French artist in the Russian service, was at the forefront of the Academy of Arts. Taisia Deville’s tombstone is an original work of Russian memorial sculpture in classical style.